Princess Nazyk - Saliev, Erkin (Kyrgyzfilm, 2012)
The seven-year-old Aidai lives with her mother Aizhan and her grandparents on Lake Issyk-Kul. Aidai draws her own fairy-tale world, where she is Princess Nazyk, the daughter of Khan Yaglakar. In reality, her mother keeps secret the father’s identity, until one day a travelling artist comes to sojourn by the lake for the summer: he is not here for the first time.